(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The development of technology has brought major changes in people’s behavior, especially in digital economic activities. One tangible form of this change is the widespread use of e-commerce in both national and international trade. Several factors arise affecting customer satisfaction which leads to the birth of legal challenges. This research is expected to contribute to the development of digital marketing strategies based on consumer behavior, while increasing the effectiveness of e-commerce businesses nationally and internationally. The research method used is normative juridical with a literature study approach, where researchers rely on various literatures to obtain research data. Electronic transactions across national borders drive business efficiency, expand consumer access to global products, and create opportunities for innovation and international collaboration. However, this condition also raises various legal challenges, such as jurisdictional uncertainty, weak consumer protection, and vulnerability to personal data breaches. Therefore, a harmonized international legal framework and strengthened national regulations are needed to ensure fair consumer protection and secure digital transactions in the era of globalization.